Problems of integration of an education system in a national innovative complex. - Abinova, А. (Journal of Economic Research & Business Administration, 2015)
Expansion of processes of globalization, development of a tendency of integration of the Republic of Kazakhstan in world educational space demand the solution of questions of system ensuring quality of vocational training in the conditions of higher education institution. In standards and the managements for system of ensuring quality in the European space of the higher education (2005) it is stated that educational institutions have to have policy and the corresponding procedures of ensuring quality of education and standards of the programs. Therefore, higher education institutions are obliged to develop and introduce strategy on improvement of quality of education. Thus strategy, policy and procedures have to possess the offi cial status and to be available to the public.